The 1st International Electronic Conference on Chemical Sensors and Analytical Chemistry 2021
DOI: 10.3390/csac2021-10455
|View full text |Cite
|
Sign up to set email alerts
|

Group 14 Metallafluorenes for Lipid Structure Detection and Cellular Imaging

Abstract: Fluorescent compounds have been shown to be useful in probing lipid dynamics, and there is ongoing interest in nontoxic, photostable, and sensitive dyes. Recently, we evaluated a number of 2,7-disubstituted-alkynyl(aryl)-3,6-dimethoxy-9,9-diphenyl sila- and germafluorenes for their potential as cellular fluorescent probes. These compounds exhibit remarkable quantum yields in hydrophobic environments and dramatic increases in emission intensity in the presence of surfactants. Here, we show that they exhibit sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In previous work, we demonstrated that this small library of 2,7-disubstituted sila-and germafluorenes interact with surfactant micelles, exhibiting impressive quantum yields in the presence of surfactants (approaching 100% quantum efficiency) and appreciable emission fold enhancements (5-25x) [20]. We also demonstrated that these compounds have specificity for lipid structures in yeast cells, colocalizing with the lipid droplet stain Nile Red [21].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…In previous work, we demonstrated that this small library of 2,7-disubstituted sila-and germafluorenes interact with surfactant micelles, exhibiting impressive quantum yields in the presence of surfactants (approaching 100% quantum efficiency) and appreciable emission fold enhancements (5-25x) [20]. We also demonstrated that these compounds have specificity for lipid structures in yeast cells, colocalizing with the lipid droplet stain Nile Red [21].…”
Section: Introductionmentioning
confidence: 62%
“…UV-Vis spectroscopy, fluorescence spectroscopy, and density functional theory (DFT) calculations are utilized. When coupled with high extinction coefficients, quantum yield, and photostability [20] [21], this class of compounds show promise as competitive probes for bioimaging and sensing.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we demonstrated that this small library of 2,7-disubstituted sila-and germa uorenes interact with surfactant micelles, exhibiting impressive quantum yields in the presence of surfactants (approaching 100% quantum e ciency) and appreciable emission fold enhancements (5-25x) [20]. We also demonstrated that these compounds have speci city for lipid structures in yeast cells, colocalizing with the lipid droplet stain Nile Red [21].…”
Section: Introductionmentioning
confidence: 62%
“…First, this substituent does influence spectral behavior ( , λ max , and quantum yield), which indicates that these substitutions can be an effective means of tuning these properties [29]. We showed that a few 2,7-disubstituted metallafluorenes can detect detergents and stain cells [63,64].…”
Section: Use Of Dft In Probe Design: 27-disubstituted Metallafluorenesmentioning
confidence: 88%